2017
DOI: 10.1021/acsmedchemlett.6b00443
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Novel, Selective GPR40 AgoPAMs

Abstract: GPR40 is a G-protein-coupled receptor expressed primarily in pancreatic islets and intestinal L-cells that has been a target of significant recent therapeutic interest for type II diabetes. Activation of GPR40 by partial agonists elicits insulin secretion only in the presence of elevated blood glucose levels, minimizing the risk of hypoglycemia. GPR40 agoPAMs have shown superior efficacy to partial agonists as assessed in a glucose tolerability test (GTT). Herein, we report the discovery and optimization of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 21 publications
4
34
0
Order By: Relevance
“…4A). The effects observed with fasiglifam are similar to those previously reported in the literature (Yabuki et al, 2013;Lu et al, 2017;Plummer et al, 2017) and are consistent with the allosteric nature of this compound.…”
Section: Gpr40 Full Agonists Induce Coupling To Ga12supporting
confidence: 90%
“…4A). The effects observed with fasiglifam are similar to those previously reported in the literature (Yabuki et al, 2013;Lu et al, 2017;Plummer et al, 2017) and are consistent with the allosteric nature of this compound.…”
Section: Gpr40 Full Agonists Induce Coupling To Ga12supporting
confidence: 90%
“…Furthermore, these properties are hypothesized to contribute to greater glucose lowering acutely in vivo with AgoPAMs compared to partial agonists. These acute data of the effects of AgoPAMs in mice were corroborated by, and extended in, diabetic GK rats where AgoPAMs were shown to have enhanced glucose lowering compared to partial agonist; an effect that was durable up to two weeks of treatment [ 5 ]. The long term effects of AgoPAM treatment on insulin and GLP-1 secretion are not known.…”
Section: Introductionmentioning
confidence: 87%
“…When the binding data obtained for compounds AMG‐837 ( 14 ), AM‐1638 ( 15 ), and AM‐5262 ( 16 ) were compared, it was observed that the last two shared the same interaction site, whereas AMG‐837 shows cooperativity with AM‐1638 and AM‐5262 by highlighting its allosteric binding behavior . This allosteric modulation can lead to superior efficacy when compared to partial agonists as the positive allosteric modulation of the full agonists increase the levels of receptor activation, which can be more than 100% of activation …”
Section: Gpr40 Agonistsmentioning
confidence: 99%
“…This recent project developed compound 19 with EC 50 = 1.1 n m and 428% of activation of GPR40. This compound showed a very promising profile for glycemic control in diabetic patients …”
Section: Gpr40 Agonistsmentioning
confidence: 99%